Community consultations for locally led anticipatory actions in key sectors for flood hazard in Matara District, Sri Lanka - Alahacoon, Niranga; Amarasinghe, H.; Indrasena, R.; Gunasundara, W.; Kaushalya, C.; Nethmi, K.; De Silva, R.; Amarnath, Giriraj (International Water Management Institute, 2025)
The community consultation workshop in the Matara District was conducted to strengthen Anticipatory Action (AA) in one of Sri Lanka’s most flood-affected regions. As flood risks intensify across the Malimboda and Thihagoda Divisional Secretariats, the workshop brought together community members, Village Disaster Management Committees (VDMCs), local authorities, and technical officers to document lived experiences, identify early actions, and improve community readiness ahead of flood events. Through interactive discussions, participatory mapping, and sector-focused group work, participants shared how floods affect their 20 Grama Niladhari (GN) Divisions differently, ranging from prolonged inundation of farmland to complete isolation of villages. These localized insights highlighted the need for context-specific early action strategies across five key sectors: Agriculture, livestock, health, education, and WASH. Community members, including women and youth, contributed valuable indigenous knowledge and coping mechanisms, fostering peer-to-peer learning and collective problem-solving. The workshop led to the development of 15 draft community-driven Early Action Protocols (EAPs), later digitized and translated for broader use. A technical session by IWMI highlighted how early warning information and forecast data, accessed through tools such as the AWARE Platform, can enhance timely decision-making and village-level preparedness. The consultation strengthened VDMC capacities, deepened community awareness, and laid the foundation for inclusive, actionable, and anticipatory action planning in the Matara District.